0149 Nuneosim Survey - A Triple Blind Study Of Nursing Perception To Simulation Training In A Tertiary Neonatal Intensive Care Setting. (1st November 2014) - Ball, Jessica; Gunda, Ranjit Kumar; Awoseyila, Adejumoke; Sharma, Alok
Abstract : Background: Simulation was endorsed by the Chief Medical Officer, Department of Health in 2008 1 and subsequently by the National Patient Safety Agency 2 as a valuable tool for training the medical workforce in the UK to address patient safety issues. Multidisciplinary simulation in neonatology increases participant's confidence in neonatal emergencies 3 and may improve patient outcome. 4 Methodology: Multiprofessional neonatal simulation programme was established in our unit in 2012. Initial feedback in 2012 has shown that the majority of participants agreed that the sessions conducted were of high quality (92%), simulation was relevant to their training (97%) and that it should be part of their training (92%). Closer scrutiny of the feedback from nurses and doctors separately has been an eye opener. Nurses were less likely to strongly agree that sessions were relevant to their training (62 vs 86%), scenarios were relevant to their clinical practice (59 vs 92%) and that post scenario multi professional feedback was relevant and useful (60 vs 84%). We have also struggled with adhoc nursing participation. After approval from local research and development department we have performed a double blind cross sectional questionnaire study to explore the nursing perception to simulation training. An initial survey was completed in May 2013 followed by curriculum mapping and incorporation of nursing facilitators. A repeat survey is to be conducted in June 2014. Results: In our initial survey we received 91 responses, results of which are being analysed by a blinded physician and results of which are blinded to both those conducting and those in the study. We aim to present the results of this and the repeat survey. We are also analysing nursing participation. Potential impact: From our study we hope to provide information addressing the challenges in implementing and sustaining multidisciplinary simulation training to other teams around the world. References: National Patient Safety Agency-NPSA. Review of patient safety for children and young people (June 2009) Donaldson L. Safer medical practice: machines, manikins and polo mints, 150 Years of the Annual Report of the Chief Medical Officer: On the State of the Public Health 2008. Department of Health, 2009; pp 49–55 Davidson SK, . Hassell, et alet al. Neonatal Simulation Training Improves Paediatric Trainees' confidence in Emergency Scenarios. Archives of Disease in Childhood - Fetal and Neonatal Edition 2014;99(Suppl 1):A64 Sharma A, Gunda R. Cascading Risk Through Multiprofessional Neonatal Simulation. Archives of Disease in Childhood - Fetal and Neonatal Edition 2014;99(Suppl 1): A35A36